Teaching hard, teaching soft a structured approach to planning and running effective training courses - Corder, Colin 1941- (Gower, 1990)
Today's trainer faces an almost endless series of difficult choices. What is the best sequence of topics? Would an exercise be more effective than a lecture? What is the appropriate teaching style for this particular group? Is there any systematic way of deciding questions like these? Yes, says the author, who suggests that both subject matter and teaching approach can be classified along a "hard/soft" spectrum. "Hard" teaching is concerned with facts, techniques and methods that typically involve correct answers, rigorous proof of mastery of a skill. "Soft" teaching covers ideas, concepts and attitudes where argument and opinion prevail. The book sets out to show how to apply this analysis to all stages of developing a training programme, and also to examine learning style and teaching styles in the light of its central theme. The book is aimed at anyone seeking a methodical approach to designing and delivering effective training.